Sacubitril/valsartan fails to prevent doxorubicin-induced cognitive impairment and hippocampal oxidative, inflammatory, and apoptotic alterations in rats - Alresheedi, Mohrah Muteb; Aldubayan, Maha Abdulrahman (Frontiers in Pharmacology, 2026)
IntroductionDoxorubicin (DOX) is a chemotherapeutic agent known for its effectiveness in treating various cancers. However, its clinical applicability is constrained by its neurotoxicity. DOX-induced toxicity is primarily driven by oxidative stress, inflammation, and mitochondrial dysfunction, resulting in elevated ROS and MDA, increased pro-inflammatory cytokines such as IL-6, IL-1β, TNF-α, and NF-κB, and increased apoptotic activity, including caspase-3 and BAX. Sacubitril/Valsartan (VS), a dual neprilysin inhibitor and angiotensin receptor blocker used in heart failure management, has shown protective effects by ameliorating inflammation and oxidative stress. This study aimed to investigate the potential of VS to mitigate or prevent hippocampal damage in rats.MethodsForty male Wistar rats were randomly categorized into four groups (n = 10 per group): Control (normal saline), DOX (2.5 mg/kg), VS (60 mg/kg), and DOX + VS. VS was administered orally once daily via oral gavage, whereas DOX was delivered intraperitoneally weekly for 4 weeks. Body weight and survival were monitored daily. Cognitive performance was assessed using behavioral tests, followed by biochemical and histological analyses. Thereafter, oxidative, inflammatory, and pro-apoptotic markers were quantified.ResultDOX and VS co-administration resulted in significant reductions in body weight and survival compared with VS-treatment alone and controls. Furthermore, both DOX treatment alone and its co-administration with VS significantly increased hippocampal levels of oxidative, inflammatory, and apoptotic markers compared with VS treatment alone and controls. In addition, histopathological analysis revealed that hippocampal tissues subjected to DOX + VS treatment exhibited severe damage, comparable to that observed in tissues treated with DOX alone. In contrast, tissues treated with VS alone and controls showed less severe damage.ConclusionCombining VS with DOX did not significantly enhance spatial learning and working memory compared with DOX alone, nor did it mitigate neuroinjury. These findings suggest that VS is not a viable therapeutic agent for alleviating DOX-induced neurotoxicity and cognitive dysfunction. This research offers novel insight for the field of pharmacological discovery by demonstrating that the neuroprotective potential of neprilysin inhibition (a key mechanism of VS) differs significantly from its cardioprotective actions. Our findings provide a foundational basis for the design of future neuroprotective therapies and for further research.